Examination of colonies and stool blots for detection of enteropathogens by DNA hybridization with eight DNA probes. - Echeverria, P (1989)
We compared three methods for detecting enteropathogens in 416 children with diarrhea: (i) examination of 10 lactose-fermenting and all non-lactose-fermenting Escherichia coli (colony blots); (ii) examination of 300 colonies (replicate blots); and (iii) determination of the total bacterial growth of stools (stool blots). All specimens were spotted onto Whatman 541 filters and hybridized with specific radiolabeled DNA probes. Enterotoxigenic E. coli was detected in 38 patients by examining colony blots, in 52 patients by examining replicate blots, and in 45 patients by examining stool blots. Enteropathogenic E. coli adhesin factor was detected in 12 patients by colony blots, in 25 patients by replicate blots, and in 16 patients by stool blots. E. coli that hybridized with the enterohemorrhagic E. coli probe was detected in 2 patients by colony blots, in 11 patients by replicate blots, and in 0 patients by stool blots. Shiga-like toxin-producing E. coli was detected in 0 patients by colony blots, in 12 patients by replicate blots, and in 0 patients by stool blots. Shigella spp. were identified by standard bacteriological methods in 82 patients, and enteroinvasive E. coli was identified by colony blots in 11 patients (total, 93), by replicate blots in 56 patients, and by stool blots in 35 patients. Of 82 culture-confirmed Shigella infections, 45 were identified by examining replicate blots with the 17-kilobase-pair probe and 36 were identified by examination with the Ipa probe (P less than 0.05). Examining replicate blots with specific probes identified more enterotoxigenic E.coli (P < 0.005), enteropathogenic E.coli adhesion factor-producing E.coli (P < 0.001), and Shiga-like toxin-producing E.coli (P < 0.005) infections than examining colony blots. More Shigella and enteroinvasive E.coli infections were identified by standard bacteriological methods and examining colony blots with a specific probe than by examining replicate and stool blots (P < 0.001).